Mapeamento de Leptospirose em comunidades quilombolas no Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Leptospirosis is a highly disseminated infectious disease that can be transmitted through direct or indirect exposure to animals, being considered a zoonosis, with its main transmission vector being the rat. Prevention of leptospirosis occurs through basic sanitation measures and dissemination of information about the risks of the disease, which is directly linked to public health. The most affected population is those with elevated risk factors for the disease, such as quilombola communities. This study aims to identify the proportion in which quilombola communities in the state of Paraná are affected by the disease. It is a basic research of descriptive and exploratory nature, with a quantitative approach, also classified as field research. The research fields were conducted in three quilombola communities located in the rural area of Castro-PR, Socavão-PR district, and Cerro Azul-PR city. Data collection was through blood samples from participants using the informed consent form. Finally, the data will be analyzed to identify the proportion of humans infected with the disease.
Keywords: Leptospirose; Comunidades Quilombolas; Saúde Pública; Saúde Única; Leptospirosis; Quilombola Communities; Public Health; One Heath; CNPQ::CIENCIAS DA SAUDE